How can we reduce bias during an academic assessment reappraisal?. (2nd November 2019) - Desy, Janeve; Coderre, Sylvain; Davis, Melinda; Cusano, Ronald; McLaughlin, Kevin
Abstract: Aims: To describe potential sources of bias during an academic assessment reappraisal and ways to mitigate these. Methods: We describe why the typical scenario of an academic assessment reappraisal – where committee members are asked to weigh contrasting accounts of past events that they did not witness, and to rate elusive constructs, such as "fairness" – is prone to multiple types of bias, including attribute substitution, default bias, confirmation bias, and impact bias . We also discuss how increased awareness of sources of bias and of debiasing strategies can improve the validity of decision making. Results: Strategies that can reduce bias in reappraisal include clearly articulating and focusing on the reappraisal question ( did bias cause a wrong decision to be made? ), educating those involved in the reappraisal of the types of bias that frequently occur in teaching and assessment (including biases that they themselves may introduce to the reappraisal), and ensuring that those involved in the reappraisal contribute equally to making decisions and recommendation. Conclusions: All academic assessments of students, particularly those that involve subjective ratings of performance, are prone to bias, which threatens the integrity of the assessment process. Given the high stakes of academic assessments, we feel that each medical school should have a process for assessment reappraisal that reduces, rather than compounds, the likelihood of wrong assessment decisions.